Antibacterial and photocatalytic effects of newly synthesized zinc oxide nanoparticles derived from Mongolian honey - Anujin Lkhagvadorj; Tserendolgor Batsukh; Altansukh Tsend-Ayush (Mongolian Journal of Chemistry)
Development of bio-compatible, bio-safe and environmentally friendly nanoparticles is a matter of urgency for research in the field of nanotechnology. In this study, we aimed to prepare zinc oxide nanoparticles from Mongolian honey as raw material and to determine its biological activities. Honey-based zinc oxide nanoparticles were obtained by green synthesis method, and their characteristics and biological activities were evaluated. Developed zinc oxide nanoparticles from Khentii honey and Selenge honey were at a size of 16.02 nm and 95.23 nm, respectively. A characteristic band of Khentii honey-based zinc oxide nanoparticles was observed at 466 cm–1 and a band of Selenge honey-based zinc oxide nanoparticles was also observed at 434 cm–1. Antibacterial and photocatalytic effects were detected for the developed nanoparticles. The study suggested that newly synthesized honey-based zinc oxide nanoparticles might be an effective tool against bacterial infection.